Pengaruh ukuran mesh permukaan logam terhadap kuat rekat geser semen resin adesif pada restorasi gigitiruan jembatan adesif Effect of metal surface mesh size to shear bond strength of adhesive resin cement to denture adhesive bridge - Edy Machmud; Moh. Dharmautama; Cencen Tjandi Yanto (Journal of Dentomaxillofacial Science, 2012)
To overcome the failure of cement adhesive bond between tooth and metal surfaces, a variety of alternative treatmentsis applied to the metal and tooth surfaces. In order to overcome this disadvantage, this study deals with the treatmenton the metal surface in mesh form. This research examined different mesh sizes of 40, 60 and 80 mesh to the metalsurface treatment in shear bond strength of adhesive resin cement. 40 pairs of upper central incisors samples wereprepared in palatal surfaces with a thickness of 0.3 mm and made a pattern of blue wax. The samples were divided intofour groups; three mesh treatment groups (40, 60 and 80) and a control group (no mesh). In the treatment groups, amesh was positioned to the opposing surface of wax pattern to the tooth preparation surface, was casted with nickelchromiumalloy, attached to the palatal surface of the teeth with adhesive resin cement, immersed in artificial salivafor 24 hours at 37Â°C. Moreover, shear bond strength test and residual resin cement on the metal surface were tested inLaboratory of the Department of Metallurgical Engineering. Data was analyzed using one-way ANOVA (p=0.05).Shear bond strength adherence of mesh plates 60 was found greater than 40, 80 and control group. Stereomicroscopeinspection of adhesive resin cement remaining on mesh 60 was similar than 40, but more than mesh 80 or controlgroup. It was concluded shear bond strength of adhesive resin cement to metal surfaces depends on the size of meshused, and shear bond strength of adhesive resin cement that still intact on the mesh surface.